Modelling soil loss from surface erosion at high-resolution to better understand sources and drivers across land uses and catchments; a national-scale assessment of Aotearoa, New Zealand. (January 2022) - Donovan, Mitchell
Abstract: Soil erosion is a significant challenge for agricultural regions, with cascading impacts to waterways, land productivity, soil carbon, and ecological health. We provide the first national-scale soil erosion model that incorporates the impacts of grazing on ground cover (Cgr ) and soil erodibility (Ktr ) into the RUSLE framework. Surface erosion rates for winter-forage paddocks (11 t ha −1 y −1 ) were substantially higher than pastoral grasslands (0.83 t ha −1 y −1 ), woody grasslands (0.098 t ha −1 y −1 ), forests (0.103 t ha −1 y −1 ) and natural soil production rates (≤1–2 t ha −1 y −1 ). Validation with empirical measurements from sediment traps, sediment cores, and chemical fingerprinting demonstrated strong linear regressions (r 2 = 0.86). Terrain impacted soil erosion directly through slope steepness and flow convergence and indirectly through strong orographic effects on rainfall erosivity (r 2 = 0.39–0.83). Annual surface erosion across Aotearoa New Zealand could reach 16.5-29.2 Mt y −1, representing ∼20M annually and up to 24–31% of sediment yield for two catchments. Graphical abstract: Image 1 Highlights: Modelled annual soil loss from surface erosion is 16.5 Mt yr −1 across New Zealand. Elevation explained up to 50% of variance in rainfall erosivity due to orographic effects. Incorporating pastoral grazing into adjusted RUSLE Ktr and Cgr improved model accuracy. Modelled soil erosion exhibited strong alignment with empirical measurements (r 2 = 0.86). Soil erosion from forage-crop paddocks is 10-fold higher than pastoral grasslands.